Regulation of cell cycle events in asymmetrically dividing cells: functions required for DNA initiation and chain elongation in Caulobacter crescentus. - Osley, M A (1978)
To study the regulation of cell cycle events after asymmetric cell division in Caulobacter crescentus, we have identified functions that are required for DNA synthesis in the stalked cell produced at division and in the new stalked cell that develops from the swarmer cell 60 min after division. The initiation of DNA synthesis in the two progeny cells is dependent upon at least two common functions. One of these is a requirement for protein synthesis and the other is a gene product identified in a temperature-sensitive cell cycle mutant. DNA chain elongation requires a third common function. The characteristic pattern of DNA synthesis in C. crescentus appears to be controlled in part by the expression of these functions in the two stalked cells at different times after cell division. The age distribution for Caulobacter cells in an exponential population has been calculated (Appendix by Robert Tax) and used to analyze some of the results.